The Kumiai traditional food system: Reconnecting nature, food and health through ancestral knowledge - Gutierrez, Carolina; Glascoe, Christine Alysse von; Bertran, Miriam; Calderon, Nelly; Villada-Canela, Mariana; Leyva, Juana Claudia (Frontiers in Sustainable Food Systems, 2022)
Traditional foods, once central to the diets of different cultures, are losing relevance as knowledge about food and its natural ecosystem deteriorates. This qualitative study describes the traditional food system of a Kumiai community in Baja California, and the ways in which the Kumiai have continually adapted their use and management of wild food resources to different food culture influences, demographic changes and contemporary food preferences. Present-day Kumiai recognize that their traditional diet was more nutritious and more connected with nature than their current diet, and express concern over transmitting existing knowledge about it to younger generations. We conclude that the characteristics of the Kumiai traditional food system not only strengthen their cultural identity and community economies, but also present potential solutions to the problem of food system sustainability by way of wild food resource management, as well as containing elements of a strategy for improving the health of community members.